PRELIMINARY PHYTOCHEMICAL SCREENING AND TO EVALUATE THE ANTHELMINTIC ACTIVITY OF HYDRO-ALCOHOLIC AND PETROLEUM ETHER EXTRACT OF NYCTANTHES ARBOUR-TRISTIS ROOT. (FAMILY-NYCTAGINACEAE) - Abdullah, Akm; Das, Sumit (International Journal of Current Pharmaceutical Research, 2018)
Objective: To estimate the anthelmintic activity of hydro-alcoholic (methanol) and petroleum ether extract of Nyctanthes arbour-tristis (family-Nyctaginaceae) in conjugation with phytochemical screening. Methods: The hydro-alcoholic and petroleum ether extract of the whole root part of the plant Nyctanthes arbour-tristis (family-Nyctaginaceae) was prepared. And studies Phytochemical constitutes by the various standard method. The anthelmintic activity of the plant was performed by a different extract of plant material were tested against adult Indian earthworms pheretima posthuma as test worms, the bioassay determines the time of paralysis and time of death. Albendazole is used as a standard reference drug. Results: The present study shows the phytochemical analysis, the anthelmintic activity of the hydro-alcoholic and petroleum ether extract of the root of Nyctanthes arbour-tristis. Various phytochemical analyses revealed the presence of alkaloids, carbohydrates, flavonoids, tannin, phenol, glycosides, saponins respectively. The anthelmintic activity of the plant extract showed significant results against all earthworms Conclusion: The study has shown that petroleum ether and methanolic extract of Nyctanthes arbortristis root have significantly determined anthelmintic activity. But the methanolic extract of Nyctanthes arbortristis root shown most significant anthelmintic activity as compared to petroleum ether extract.